Air enema versus barium enema in intussusception: an overview - Al-Mubarak, Lujain; Alghamdi, Eman; Alharbi, Saad; Almasoud, Hidayah; Al-Ali, Naseem; Mujurdy, Shrooq; Alamro, Amro; Nagadi, Albatoul; Alsharif, Alhareth; Almugbel, Saad (International Journal Of Community Medicine And Public Health, 2018)
Intussusception is a common cause of intestinal obstruction in paediatric population. It is a medical emergency that necessitates prompt reduction of intussuscepting bowel. If left untreated, intussusception can be fatal in a couple of days. The mainstay treatment of intussusception is enema reduction. Both barium and air enema reduction techniques are successful and acceptable strategies for management of intussusception in children. The use of air reduction is currently growing for its safety. Air reduction is associated with higher success rates, less risk for perforation, and less risk for peritoneal contamination than barium reduction. Air reduction generates higher intraluminal pressure during the reduction procedure thus making it faster and more effective. Barium reduction, on the other side, has a diagnostic potential and can better detect pseudo-reduction after management of intussusception. It is easier to perform and more familiar for most of the radiologists than air reduction. To date, both techniques are used, and the choice depends largely on clinical practice, institutional guidelines, and radiologists’ preference. This article aims at differentiating between the two types of reduction regarding the technique, advantages, disadvantages, success rates, recurrence rates, and complications rates.